Cultivating Problem-Solving in Undergraduate Chemistry Teachers: A Review of Pedagogical Strategies and Curriculum Design - Ahmad, Fandi; Sari, Nur Indah (Pusat Studi Bahasa dan Publikasi Ilmiah, 2025)
The development of problem-solving skills in prospective chemistry teachers is a fundamental aspect of education. This study aims to review pedagogical strategies and curriculum design that cultivate problem-solving in undergraduate chemistry teachers. This literature review uses three main steps: 1) Comprehensive Search Strategy to identify relevant studies related to pedagogical strategies and curriculum design; 2) Screen and Select Relevant Studies based on criteria relevant to problem-solving development; and 3) Synthesize and Analyze Findings to systematically combine and interpret selected data to produce a deeper and more comprehensive understanding. The results of the literature review indicate: 1) Effective pedagogical strategies include computer-based learning, guided inquiry, and context-based learning. 2) Curriculum designs such as innovative teaching programs, vocational learning, and laboratory curricula by integrating technology. Collaborative curriculum models and virtual learning systems based on constructivism are essential. Pedagogical strategies and holistic curriculum designs that focus on developing critical and adaptive individuals are essential to equip prospective chemistry teachers with complex problem-solving skills.